KEMENANGAN KEMBALI MANTAN BUPATI AMAT ANTONO PADA PILKADA KABUPATEN PEKALONGAN TAHUN 2011 - Gulun A Maula; Purwoko .; Muh Adnan (Journal of Politic and Government Studies, 2013)
Abstract Antono Amat served as regent of Pekalongan Regent period 2001-2006 he’s failed to nominate in period 2006-2011 and he ran again in 2011-2016 election period. Be interesting to review because he’s wins again on election Pekalongan regency although failed in the previous period. The winning strategy Amat Antono viewed from various perspectives, not only viewed from the strategy Amat Antono and team but also view from the public of distric Pekalongan. Amat Antono strategy used is imaging before campaign period, create togetherness with the audience, optimize activity on campaign period, and secure the voters in the cooling period. Not only that, the desire of public who want Mr Antono as leader in the Pekalongan regency is also an influential factor the back victories the former regent Pekalongan. Keywords: local election, win back